Human bone marrow adipocytes display distinct immune regulatory properties - Miggitsch, Carina (EBioMedicine, 2019)
BACKGROUND: The bone marrow (BM) is a major reservoir of resting memory T cells and long-lived plasma cells, capable of providing protection against recurrent infections. Whether the age-related accumulation of adipose tissue in the BM affects the functionality and maintenance of memory cells is not well understood. METHODS: For the first time, we compare human femur marrow adipose tissue (fMAT) and subcutaneous white adipose tissue of the thigh (tsWAT) obtained from the same donors. Therefore, we used microarrays for comparative global gene expression analysis, and employed assays to analyse parameters of adipocyte biology, inflammation and oxidative stress. FINDINGS: We show that fMAT adipocytes differ significantly from tsWAT adipocytes regarding specific gene expression profiles including inflammatory responses and adipogenesis/adipocyte phenotype. Concomitant with considerably lower levels of CD36, a membrane-associated protein important for long-chain fatty acid uptake that is used as maturation marker, fMAT adipocytes are smaller and contain less triglycerides. fMAT adipocytes secrete similar levels of adiponectin and leptin as tsWAT adipocytes, and express increased levels of pro-inflammatory molecules concomitant with an elevated generation of reactive oxygen species (ROS) and impaired function of plasma cells in the BM. INTERPRETATION: Our findings suggest that fMAT is a unique type of adipose tissue containing small adipocytes with lower CD36 protein and triglyceride levels than tsWAT but high adipokine secretion. Moreover, fMAT adipocytes secrete high levels of pro-inflammatory cytokines, contributing to inflammation and impairment of plasma cell function in the BM, suggesting that fMAT has more immune regulatory functions than tsWAT.